2017
DOI: 10.1038/s41467-017-01427-1
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to TGFβ suppression and improved anti-tumor responses in CD8+ T cells lacking PTPN22

Abstract: Transforming growth factor β (TGFβ) is important in maintaining self-tolerance and inhibits T cell reactivity. We show that CD8+ T cells that lack the tyrosine phosphatase Ptpn22, a major predisposing gene for autoimmune disease, are resistant to the suppressive effects of TGFβ. Resistance to TGFβ suppression, while disadvantageous in autoimmunity, helps Ptpn22 −/− T cells to be intrinsically superior at clearing established tumors that secrete TGFβ. Mechanistically, loss of Ptpn22 increases the capacity of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 41 publications
8
44
0
Order By: Relevance
“…Brownlie et al has reported resistance to TGF-β suppression and improved antitumor responses in CD8 + T cells lacking PTPN22. 20 De Meulenaere et al has reported that CD8 + T lymphocytes constitute an independent prognostic marker in patients diagnosed with oropharyngeal squamous cell carcinoma. 21 In our study, CD8 + cells are significantly associated with improved OS.…”
Section: Discussionmentioning
confidence: 99%
“…Brownlie et al has reported resistance to TGF-β suppression and improved antitumor responses in CD8 + T cells lacking PTPN22. 20 De Meulenaere et al has reported that CD8 + T lymphocytes constitute an independent prognostic marker in patients diagnosed with oropharyngeal squamous cell carcinoma. 21 In our study, CD8 + cells are significantly associated with improved OS.…”
Section: Discussionmentioning
confidence: 99%
“…Also of notice, a pronounced number of critical immunomodulators, which were described in an immunogenomic analysis of major TCGA cancer data sets and included PDCD1LG2, BTN3A2, GZMA, BTLA, CD28, ICOS, and IDO1, were contained in the 358 DEG set [69]. The intracellular phosphatase PTPN22 is implicated in immune cell signaling and known as a predisposing gene for autoimmune diseases [70]. A non-synonymous polymorphism in this gene is associated with enhanced susceptibility to a variety of autoimmune diseases [71].…”
Section: Non-intersecting 358 Deg Set Derived From the Comparison Gromentioning
confidence: 99%
“…As a consequence of enhanced TCR signalling and concomitant reduced susceptibility to TGFb, upon adoptive transfer, tumourreactive PTPN22-deficient CD8 + T-cells were better able to control the growth of established tumours that secreted TGFb than wild-type T-cells. 64 These data suggest that deleting PTPN22 in human TILs or TAA-specific T-cells may improve the efficiency of T-cell immunotherapy of human cancer.…”
Section: Ptpn22 and Anti-tumour Responsesmentioning
confidence: 92%
“…Previous data showed that TGFβ plays a critical role in controlling autoreactive and anti‐tumour T‐cell responses, particularly to weak, self‐ligand‐mediated responses . Interestingly, PTPN22‐deficient CD8 + T‐cells were highly resistant to the suppressive effects of TGFβ . This reduced susceptibility to TGFβ was not a consequence of alterations in canonical TGFβ‐receptor signalling.…”
Section: Ptpn22 and Anti‐tumour Responsesmentioning
confidence: 94%
See 1 more Smart Citation